Transparency Analysis Of Financial Report Preparation And Village Fund Management In Padang Mumpo Village, Pino District, South Bengkulu Regency - Wahyuni, Reska; Wagini, Wagini; Astuty, Kamelia (Journal of Management, Economic, and Accounting, 2024)
Research objectives To determine and analyze the transparency of village financial management in Padang Mumpo Village, Pino District, South Bengkulu Regency. The method used is a qualitative method. Data collection techniques are observation, documentation and interview techniques, then adjusted to the indicators of the Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management and outlined in text form. The results of this study Padang Mumpo Village always provides information to the public and always reports accountability, and there is auditing by the inspectorate, therefore it can be concluded that the Transparency of Financial Reports and the management of Village Funds in Padang Mumpo Village based on indicators, namely the Regulation of the Minister of Home Affairs Number 20 of 2018 concerning Village Financial Management is in accordance.